1997
DOI: 10.1029/97gl03160
|View full text |Cite
|
Sign up to set email alerts
|

The polarization of auroral radio emissions

Abstract: Abstract. Ground level observations using two vertical loop antennas oriented at 900 to each other reveal the sense of polarization of several types of auroral radio emissions in the frequency range 30-5000 kHz. Auroral hiss is observed to be right elliptically polarized

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
43
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 47 publications
(48 citation statements)
references
References 11 publications
5
43
0
Order By: Relevance
“…The MF burst can be identified as broadband emissions covering from 1.9 to 2.6 MHz appearing only in the LH spectra. The polarization character of this MF burst event is consistent with the result reported by Shepherd et al (1997). However, it is noted that the present event lasts for only a short time period (10 s), while the typical duration has been reported to occur for about several minutes (Weatherwax et al, 1995;LaBelle et al, 1997).…”
Section: Mf Burst (September 23 and October 28 2006)supporting
confidence: 81%
See 1 more Smart Citation
“…The MF burst can be identified as broadband emissions covering from 1.9 to 2.6 MHz appearing only in the LH spectra. The polarization character of this MF burst event is consistent with the result reported by Shepherd et al (1997). However, it is noted that the present event lasts for only a short time period (10 s), while the typical duration has been reported to occur for about several minutes (Weatherwax et al, 1995;LaBelle et al, 1997).…”
Section: Mf Burst (September 23 and October 28 2006)supporting
confidence: 81%
“…MF burst shows a broadband impulsive feature with a bandwidth of 1-2 MHz in a frequency range of 0.8-4.5 MHz (LaBelle et al, 2005). The polarization character of 2 f ce roar and MF burst have been identified as left-handed polarized waves by Shepherd et al (1997), implying that they should propagate in the L-O mode in the ionosphere.…”
Section: Introductionmentioning
confidence: 99%
“…Because these frequency bands are considered to be close to the second and third harmonics of the electron cyclotron frequency in emission sources, each type of auroral roar is called 2f ce and 3f ce roars. The polarization character of 2f ce and 3f ce roars was identified as left-handed polarized waves by Shepherd et al [1997] and Sato et al [2008]. Both types are commonly attributed to mode conversion to the L-O mode of upper hybrid waves excited in the bottomside ionosphere by auroral electrons [e.g., LaBelle and Treumann, 2002].…”
Section: Introductionmentioning
confidence: 99%
“…First reported by Weatherwax et al [1994], it is a bursty broadband emission between 1.3 and 4.5 MHz, observed for a few minutes around substorm onset, often coincident with auroral hiss, 2f ce and 3f ce auroral roar, and substorm-correlated absorption of AM broadcast band stations. LaBelle et al [1997] present 10 kHz bandwidth waveform measurements suggesting substructure with timescales as short as 100-300 ms. Shepherd et al [1997] determined that MFB is left-hand polarized. Using data from the South Pole Station, LaBelle et al [2005] demonstrated that MFBs are observed at ground level only during darkness and that their occurrence rate is primarily dictated by magnetic time, maximizing during premidnight hours, and that the frequency range of MFB varies characteristically with solar zenith angle.…”
Section: Introductionmentioning
confidence: 99%